Settlement of Credit Problems in Four Wheel Motorized Vehicle Financing Agreements at PT. BCA Finance Jayapura Branch - Pelupessy, Eddy (Journal of Progressive Law and Legal Studies, 2023)
This research was conducted with the aim of finding out and analyzing the resolution of problem loans in four-wheeled motor vehicle financing agreements at BCA Finance Jayapura Branch as a Financing Institution for consumers and obstacles in resolving problematic credit in four-wheeled motorized vehicle financing agreements at BCA Finance Jayapura Branch as a Financing Institution to consumers. This research method is a type of empirical research, observation/survey. Observational/survey research is included in the category of observational research using a survey method, namely: the researcher directly conducts research at a predetermined location by observing and using interviews to obtain/obtain the necessary data. The results of the research reveal that the resolution of bad credit or problem credit taken by BCA Finance Jayapura Branch is generally carried out by internal settlement first through the Service Department and the Problem Account Officer (PAO) Department using deliberation and consensus. Therefore, the pattern of preventing the occurrence of problematic or potentially bad credit in distributing credit financing facilities by financial institutions to consumers must pay attention to the principle of prudence (doctrine of prudence) such as basic principles: character, capacity, capital, collateral, condition of economic, and it is necessary to carry out checks and balances and immediate checks on the validity and authenticity of the documents that are relied upon. So that it doesn't happen that financing institutions only pursue consumer quantity targets and then ignore matters relating to consumer quality, security of the parties and creditworthiness.